FAKTOR YANG MEMPENGARUHI PERSEPSI MAHASISWA TERHADAP VAKSINASI COVID-19 - Ratna Juwita; Rummy Islami Zalni; Zurni Seprina; Yeffi Masnarivan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The Implementation of the covid-19 vaccinationis a Government PolicyIn order to contain the spreading of the COVID-19 pandemic. It is has experienced many obstacles,one of them is rejection from the society, including students.It is triggered becausea lot of news circulating on social media such as Facebook, Youtube, Instagram, WhatsAppand other mediaregarding negative news about the Covid-19 vaccineboth from within and outside the country. The news has an impact on the perception of the socieity and studentsabout the effectiveness and efficacy of vaccines. Results of the initial survey conducted in May 2021 of 20 students, it was found that not one student has been vaccinated the Covid-19. The purpose of this research isto determine the factors that influence student perceptions of the Covid-19 vaccination.This type of research is quantitative with a cross sectional approach. The population in this study were all regular students at Tengku Maharatu are 124 students. sample taken in total. Data were analyzed by univariate and bivariate.The result of the study showed that there is a very significant relationshipbetween knowledge, the issue of Covid 19 vaccination and education with students perseptions of the Covid-19 vaccination p value0,011, 0,003 dan 0,000.